Esophageal Stricture Post Accidental Corrosive Ingestion: A Case Report - Joshi, Binita Gurubacharya; Lamichhane, Ritu; Ghimire, Madhu (Journal of Nepal Paediatric Society, 2017)
Corrosive substance ingestion is a seriouspublic health hazard. Mostly, children are victim due to accidental ingestion occurring commonly in less than five years. Whether acid or alkali, the ingestion may have catastrophic effects and the outcomes can vary from minimal injury to perforation and death. Esophagogastroduodenoscopy should be done 12-24 hours of ingestion in order to assess the extent of mucosal injury. Esophageal stricture remains one of the major sequel usually seen after three weeks of ingestion. Endoluminal dilatation is current recommendation for initial treatment of stricture and surgery should follow for strictures refractory to dilatation. We here present a case of a five year old child with accidental corrosive ingestion at her school which led to esophageal stricture. She underwent multiple dilatation of stricture followed by esophageal corrective surgery which again led to post-surgical stricture requiring further dilatations.